(untitled) (Veterinary Science, 2020)
A simulation model was designed in order to serve as a management tool to estimate the rate of change in live weight in confined steers. The main components of the production system integrated in the model were the animal, the environment and the diet. The quantified biological interrelationships are summarized in the voluntary consumption of dry matter and nutritional balances of metabolizable energy and digestible protein. The potential consumption estimated by the physiological maturity dependent on the zebu, bullfighting or hybrid animal biotype, sex and age was corrected by indexes related to the size of the food particle and actual digestibility of the diet. This was estimated through the development and validation of indexes and correction functions considering the level of tannins, silica, crude protein and non-structural carbohydrates together with the particle size taken from data tables of the Cornell model. The confidence of the model to predict the increase rate in live weight was evaluated by means of the t student test with experimental data from 12 batches of steers of breeds of early physiological maturity, during 119 days. The daily gains of average weights of the model presented a similar trend to the observed data (P: 0.65). In addition, the regression analysis between simulated and observed variables presented a similar trend both for estimating consumption (R2 = 0.62) and for estimating daily weight gain (R2 = 0.58). The model allows evaluating process innovations to determine production functions related to live weight in different scenarios incorporating variables such as bovine biotype, modified diet quality based on its digestibility, particle size, and environmental temperature.